2013
DOI: 10.1177/0266666913477430
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of health data quality management and best practices at community and district levels in LMIC

Abstract: Research findings have reported lack of reliable health data and poor management for district health information systems in low and middle-income countries (LMIC). This paper aims to review the literature on problems with health data quality management and health information evidences and evidences of best practices and use at community and district levels in LMIC, with a view to making recommendations for future research. Research citations, conference proceedings and diseases surveillance reports from 2000–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 38 publications
1
57
0
1
Order By: Relevance
“…10 A summary of English studies are shown in Table 1. The framework for managing the quality of university educational information was evaluated, based on the literature, in 5 main categories of information quality and its importance, characteristics of information quality, a comparative study of the models of DQM, improving information quality and university policies about DQ.…”
Section: Resultsmentioning
confidence: 99%
“…10 A summary of English studies are shown in Table 1. The framework for managing the quality of university educational information was evaluated, based on the literature, in 5 main categories of information quality and its importance, characteristics of information quality, a comparative study of the models of DQM, improving information quality and university policies about DQ.…”
Section: Resultsmentioning
confidence: 99%
“…We believe this is an impressive capture rate, especially given the previously documented challenges with health records utilisation and management in sub-Saharan countries. [24][25][26] Furthermore, interobserver agreement among data abstractors was high, with the calculated Cohen's κ value representing 'almost perfect' agreement according to the classification of Landis and Koch. 14 Nearly 30% of children were tested for HIV either in the ED or in the inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of health data quality in LMICs, investigators identified multiple critical weaknesses, including missing data, unreliable clinical information entered into electronic records, problems with timeliness, and limited accessibility. 92 One important challenge to the development of scalable, sustainable mHealth services is the limited infrastructure for training and supporting the workforce in LMICs with skills in health informatics. 93 Several programs for building the needed human capital have been launched, with support by the US Fogarty International Center, the Bill and Melinda Gates Foundation, and the American Medical Informatics Association.…”
Section: Discussionmentioning
confidence: 99%